Supervisory Function Analysis of the DPRD on the Tourism Governance Policy of Batu City (Study on the Batu City DPRD) - Sonia Sonia; Salahudin Salahudin (Universitas Teuku Umar, 2023)
This study aims to analyze and describe how the implementation of the supervisory function and strategy of the Batu City DPRD towards tourism governance in Batu City. In tourism development projects in Batu City, the DPRD has a role as an actor in making regulations or approvals before the development runs. The supervisory function of regional regulations is very important which provides an opportunity for the DPRD to be more active and creative in responding to various obstacles to the implementation of regional regulations. Supervision of regional administration is a process of activities whose purpose is to ensure that local government runs effectively and efficiently in accordance with the plans and provisions of laws and regulations. Therefore, the author here will analyze the supervisory function of tourism governance policies in Batu City to find out whether the tourism development program is running in accordance with the governance policies known by the DPRD. The research methods applied to this study are qualitative research methods for content analysis and interviews with staff of the Batu City DPRD secretariat regarding the supervisory function. The results of the study revealed that the potential for tourism governance in Batu City has several aspects. The outcomes of the study helped shape and advance the supervisory role, specifically with regards to the execution and administration of tourism in Batu City. The limitation in this study is that the data used is still limited to the type of skunder data, namely documents and journals related to tourism governance in Batu City. The next research needs to use skunder data.